Pengaruh Penerapan Good Corporate Governance Terhadap Integritas Laporan Keuangan Pada Perusahaan Manufaktur Sektor Makanan Dan Minuman Yang Tercatat di Bursa Efek Indonesia Tahun 2014-2016 - B1031141071, Desy Christina (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
This study aims to examine the influence of Good Corporate Governance on the Integrity of Financial Statements in food and beverage manufacturing companies. Financial Statement Integrity is measured using conservatism assuming non-operating accruals. GCG mechanism is proxied with four variables: Institutional Ownership, Managerial Ownership, Audit Committee, and Independent Commissioner. This study shows that Good Corporate Governance as represented by the variable of Institutional Ownership, Audit Committee, and Independent Commissioner has no significant effect on Financial Statement Integrity. While Good Corporaye Governance which is represented by Managerial Ownership variable has a significant effect on Financial Statement Integrity.Keywords: Good Corporate Governance, Integrity of Financial Statement, Institutional Ownership, Managerial Ownership, Audit Committee, and Independent Commissioner.